Artefak Kolonial Perkebunan Panglejar, Maswati, Rajamandala Masa Hindia Belanda: Arti dan Arah Sejarah: Arti Dan Arah Sejarah - Lia Nuralia (JURNAL PANALUNGTIK, 2020)
Colonial plantation artifacts are an important cultural in the history of plantation at Bandung, West Java. What and how the plantation artifacts are the main problem in this paper. the purpose of this paper is to explain the colonial plantation artifacts in the form of inscriptions and old maps of the garden. The method used is a desk research on archeological research reports, books, and the internet. The data sources obtained are the inscription of the establishment of the old Panglejar tea factory in the IHT Building, the inscription of the establishment of the Administrator of Maswati Plantation house in the Pusdiklat Building, and the old map of the Rajamandala P lantation in the Office of Rajamandala Afdeling 1 of Panglejar Platation. The three colonial artifacts give special meaning to the continuity of plantation history since the days of the Dutch East Indies until now, as well as showing directions to search for and find historical information through colonial archival research and information from interviews with relevant informants at the present time.